1997
DOI: 10.1046/j.1365-2958.1997.5061868.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the Saccharomyces cerevisiae ATP‐binding cassette transporter protein Ycf1p

Abstract: SummaryYcf1p is a member of the ATP-binding cassette transporter family of membrane proteins. Strong sequence similarity has been observed between Ycf1p, the cystic fibrosis transmembrane conductance regulator (CFTR) and multidrug resistance protein (MRP). In this work, we have examined the functional significance of several of the conserved amino acid residues and the genetic requirements for Ycf1p subcellular localization. Biochemical fractionation experiments have established that Ycf1p, expressed at single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 35 publications
2
55
0
Order By: Relevance
“…MD was also included in the assay. We found that overexpression of (43). Similarly, overexpression of YAP1 in MRY13-1A caused a significant level of resistance to DEM that was reduced by the flr1⌬ deletion, demonstrating that YAP1 overexpression confers resistance to DEM and that FLR1 contributes to this resistance.…”
Section: Flr1 Transactivation Upon Toxic Stress Is Mediated By Yap1p mentioning
confidence: 54%
“…MD was also included in the assay. We found that overexpression of (43). Similarly, overexpression of YAP1 in MRY13-1A caused a significant level of resistance to DEM that was reduced by the flr1⌬ deletion, demonstrating that YAP1 overexpression confers resistance to DEM and that FLR1 contributes to this resistance.…”
Section: Flr1 Transactivation Upon Toxic Stress Is Mediated By Yap1p mentioning
confidence: 54%
“…Examples include the antioxidant/oxidizing agents diamide and 1-chloro-2,4-dinitrobenzene (94,163). A potentially useful Ycf1p substrate that has yet to be fully exploited is monochlorobimane, which can be added to living yeast cells and visualized by fluorescence microscopy.…”
Section: Ycf1pmentioning
confidence: 99%
“…This (102,103). An unusual aspect of Ycf1p biology is that this transporter is posttranslationally processed to yield N-and C-terminal cleavage products that are stable and remain tightly associated with one another (102,163). Cleavage occurs within luminal loop 6 (L6) in a region representing an insertion that is specific to Ycf1p (Fig.…”
Section: Ycf1pmentioning
confidence: 99%
“…Does Tus1 activate Rho1 on the vacuolar membrane? Rho1 localizes to the plasma membrane and to other sites including bud tips, the mother-bud neck, and endomembranes (McCaffrey et al 1991;Drgonova et al 1996;Qadota et al 1996;Yoshida et al 2009), while Ycf1 localizes to the vacuolar membrane (Wemmie and Moye-Rowley 1997;Mason and Michaelis 2002). Tus1 localizes to the presumptive bud site in unbudded cells and to the mother-bud neck during cytokinesis (Yoshida et al 2006;Kono et al 2008), but has not been observed on the vacuolar membrane.…”
mentioning
confidence: 99%